Cultivating Divine Love via Lailat al-Qadr: Insights from Mosque Dhikr Gatherings - Aang Mahyani; Supiana Supiana (International Journal of Nusantara Islam, 2026)
Mahabbah, derived from the root word habba, refers to a profound emotional attachment and enduring devotion of a servant to God, representing a central element of Islamic spirituality. Closely associated with Lailatul Qadar, the holiest night during the last ten days of Ramadan, mahabbah functions not only as a personal expression of divine love but also as a foundation for collective religious consciousness and social responsibility. This study aims to examine how the members of the Majelis Dhikr at Nurul Huda Mosque in Kampung Kudang, Bandung, cultivate love for Allah through consistent religious gatherings and communal engagement, particularly in preparation for Lailatul Qadar. Using a qualitative descriptive method supported by interviews and documentation, the findings reveal that the practices of dhikr, Qur'anic learning, and social initiatives significantly influence the moral character and behavior of the participants, fostering a culture of compassion, solidarity, and mutual assistance. This integration of spiritual devotion with social action illustrates how religious values can shape a transformative community life. The study concludes that a sustained approach to Lailatul Qadar through structured communal worship contributes to deeper spiritual awareness and reinforces a socially engaged religious identity within contemporary Muslim society.